(untitled) (Indian Journal of Animal Production and Management, 2015)
The present study was conducted to assess the immunological and antioxidant effect of fresh Azolla supplementation on Vanaraja chicken. Two hundred fifty six one week-old birds were distributed into 4 dietary treatments (C1, T1, T2, T3) with 3 replicates each supplemented with 0, 5, 10 and 15% dietary protein from fresh Azolla, respectively. The experiment continued up to 10 weeks of age. At the 56th day of age Cutaneous Basophilc Hypersensitivity (CBH) test as cellular immune response and antibody titre against SRBC as humoral immunity response were determined. The weight of lymphoid organs, antioxidant enzyme, and lipid peroxidation activity were determined at 10th week of age. The cellular and humoral immune response and weight of lymphoid organs exhibited non-significant (P>0.05) difference between the treatment groups. Erythrocyte catalase activity was significantly (P<0.05) higher in Azolla supplemented groups compared to the control group where as the erythrocyte malondialdehyde (lipid peroxidation activity) level between the treated groups did not show any significant (P>0.05) difference. Liver histopathology revealed absence of any deleterious effect of Azolla on Vanaraja chickens.